The age of Wolfe Creek meteorite crater (Kandimalal), Western Australia. (1st September 2019) - Barrows, Timothy T.; Magee, John; Miller, Gifford; Fifield, L. Keith
Abstract: Wolfe Creek crater lies in northwestern Australia at the edge of the Great Sandy Desert. Together with Meteor Crater, it is one of the two largest craters on Earth from which meteorite fragments have been recovered. The age of the impact is poorly constrained and unpublished data places the event at about 300, 000 years ago. In comparison, Meteor Crater is well constrained by exposure dating. In this paper, we present new ages for Wolfe Creek Crater from exposure dating using the cosmogenic nuclides 10 Be and 26 Al, together with optically stimulated luminescence ages (OSL) on sand from a site created by the impact. We also present a new topographic survey of the crater using photogrammetry. The exposure ages range from 86 to 128 ka. The OSL ages indicate that the age of the impact is most likely to be 120 ka with a maximum age of 137 ka. Considering the geomorphic setting, the most likely age of the crater is 120 ± 9 ka. Last, we review the age of Meteor Crater in Arizona. Changes in production rates and scaling factors since the original dating work revise the impact age to 61.1 ± 4.8 ka, or 20% older than previously reported.